การรับรู้ระดับคุณภาพการบริการแยกตามคุณลักษณะประชากรศาสตร์ของการไฟฟ้าส่วนภูมิภาค จังหวัดกาฬสินธุ์ - ลาวงศ์, ศุภกร; ศิริมงคล, ฐิตารีย์ (Journal for Developing the Social and Community, 2023)
This study is a survey study. The purposes of this study were 1) to study electricity users’opinions toward sevice of Provincial Electricity Authority in Kalasin Province and 2) to compare service quality of Provincial Electricity Authority in Kalasin Province Classified by Demographic Characteristics and type of electricity usage. Questionaires were used as a research instrument. The samples consisted 353 elctricity users who got the service of Provincial Electricity Authority in Kalasin Province by selecting new applicants for electricity service including Convenience sampling. Statistics used in the study were mean, percentage, average, and standard deviation, t - test to test the difference of means from two samples using statistics One - way ANOVA. In one - way analysis of variance and comparison of differences, pairwise tests were performed using LSD method. The level of statistical significance was set at 0.05. The results of the research revealed that the perceived level of service quality classified according to demographic characteristics of the Provincial Electricity Authority users in Kalasin Province was overall at a very good level in all aspects with a total mean of 4.59. When analyzing each aspect, it was found that the aspect with the highest overall average was staff’s good manners and attentiveness of service and quality of equipment with the same average of 4.63, followed by the value of the price compared to the service received has an average of 4.60, the next rank is various technologies are used to increase service efficiency with an average of 4.58. Convenience and speed of service in each process had an average of 4.57. The variety of service choices or convenient to contact had an average of 4.51 which is the least. And a comparison of the service quality of service quality perception classified by demographic characteristics of the Provincial Electricity Authority in Kalasin Province classified by gender, age, and education level, average monthly income and different types of electricity usage, their opinions on service quality of the Provincial Electricity Authority in Kalasin Province differed significantly at the 0.05 level.